2011
DOI: 10.1177/0007650310394642
|View full text |Cite
|
Sign up to set email alerts
|

Green Governance: Boards of Directors’ Composition and Environmental Corporate Social Responsibility

Abstract: This study contributes to the work on board composition and firm corporate social responsibility by extending it to the environmental domain. It evaluates the relationship between boards of directors’ composition and environmental corporate social responsibility (ECSR) by integrating literatures on board composition, firm corporate social responsibility, and individual differences in attitudes toward and information about environmental issues. Using disclosed company data and the natural environment ratings da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

85
877
15
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 867 publications
(1,105 citation statements)
references
References 95 publications
85
877
15
22
Order By: Relevance
“…Consistent with these arguments, Mallin and Michelon (2011) find a positive link between a number of board attributes including board independence and gender diversity on the board. Similar results are also found by Post et al (2011) who find that firms with higher proportion of outside directors and those with three or more female directors tend to have higher Kinder Lydenberg Domini (KLD) strengths scores. Webb (2004), who investigates the differences in the structure of the board of directors between socially responsible and matched non-responsible firms, also finds that socially responsible firms tend to have larger boards, more independent board members, and more women on their boards.…”
Section: Literature Review Theoretical Model and Hypothesis Developsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with these arguments, Mallin and Michelon (2011) find a positive link between a number of board attributes including board independence and gender diversity on the board. Similar results are also found by Post et al (2011) who find that firms with higher proportion of outside directors and those with three or more female directors tend to have higher Kinder Lydenberg Domini (KLD) strengths scores. Webb (2004), who investigates the differences in the structure of the board of directors between socially responsible and matched non-responsible firms, also finds that socially responsible firms tend to have larger boards, more independent board members, and more women on their boards.…”
Section: Literature Review Theoretical Model and Hypothesis Developsupporting
confidence: 81%
“…To this end, a firm has to have the right mix of directors, particularly outside directors who can bring the diversity of knowledge, skills, experience, expertise, and ties (Fama and Jensen 1983;Pfeffer and Salancik 1978); as well as a broader stakeholder orientation (Wang and Dewhirst 1992) that can help develop an effective CSR strategy leading to superior CSR performance. Consistent with such arguments, studies tend to find a positive association between the proportion of outside directors including women directors and various measures of CSR performance (Mallin and Michelon 2011;Post et al 2011;Webb 2004). For example, Mallin and Michelon (2011) draw upon the RDT and argue that, as providers of both human and relational capital, outside directors and women directors can enhance a firm's social performance and its reputation by developing useful relationships with the firm's stakeholders.…”
Section: Literature Review Theoretical Model and Hypothesis Developmentioning
confidence: 95%
See 1 more Smart Citation
“…Zhang [147] focused on a sample of 475 publicly traded Fortune 500 companies and found that more outside directors has a positive influence on CSP. Post et al [131] analyzed 78 Fortune 1000 firms and found a positive connection between board independence and CSP, measured by Kinder, Lydenberg and Domini (KLD) ratings.…”
Section: Linking Board Independence and Corporate Social Performancementioning
confidence: 99%
“…CSR) remains under-researched. The very few studies which examine the relationship between corporate responsibility and board diversity point out the positive effects on some of the CSR aspects using quantitative measures (Bear et al, 2010;Coffey & Wang, 1998;Post, Rahman, & Rubow, 2011;Rao & Tilt, 2015;R. J. Williams, 2003).…”
Section: Introductionmentioning
confidence: 99%